A Case Report on Congenital Hyperinsulinism Associated with ABCC8 Nonsense Mutation: Good Response to Octreotide - Hussain, Suhaimi; Flanagan, Sarah; Ellard, Sian (Journal of the ASEAN Federation of Endocrine Societies, 2016)
A 2.4 kg baby boy born via Caesarian section at 35 weeks had the first onset of hypoglycemia at 2 hours of life. The infant required a glucose load of 30 mg/kg/min. Insulin level was 19.6 pmol/L (normal value 17.8-173.0) in the absence of ketosis. He was resistant to oral diazoxide but responded to octreotide infusion. The boy was found to be heterozygous for an ABCC8 nonsense mutation, p.R934*. We present our experience on the use of subcutaneous octreotide for 2 years for the treatment of diazoxide resistant congenital hyperinsulinism (CHI).